Strategi Marketing Politik Pasangan Anies Baswedan-Sandiaga Uno pada Putaran Pertama Pemilihan Gubernur DKI Jakarta Tahun 2017 - Stahl, Ichdaf; Apriani, Kadek Dwita; Jayanthi Mertha, A.A. Sg. Mirah Mahaswari (Jurnal Nawala Politika, 2022)
This research attempts to determine political marketing of Anies-Sandi in the first round of the 2017 Jakarta Governor Election by using the 4P political marketing theory by Niffenegger which is a strategy used by candidates in campaign activities that aim to influence voters during the general election. This strategy was used as a political communication tool towards society to branding their visions and missions, then became the focus of this research. The results indicate that Anies-Sandi have well-applied the principles of political marketing strategies with the 4P concept, namely product, promotion, price, and place. As the winning team and volunteers do the marketing of their political products during the campaign through media and publications, by calculating costs and candidate images, as well as information dissemination strategies through winning posts spread out across every area of Jakarta. With the result that Anies-Sandi won the 2017 Jakarta Governor Election.